Effect of Oral Docosahexaenoic Acid (DHA) Supplementation on DHA Levels and Omega-3 Index in Red Blood Cell Membranes of Breast Cancer Patients - Molfino, Alessio; Amabile, Maria I.; Mazzucco, Sara; Biolo, Gianni; Farcomeni, Alessio; Ramaccini, Cesarina; Antonaroli, Simonetta; Monti, Massimo; Muscaritoli, Maurizio (Frontiers in Physiology, 2017)
Rationale: Docosahexaenoic acid (DHA) in cell membrane may influence breast cancer (BC) patients' prognosis, affecting tumor cells sensitivity to chemo- and radio-therapy and likely modulating inflammation. The possibility of identifying BC patients presenting with low DHA levels and/or low ability of DHA incorporation into cell membrane might help to treat this condition. Methods: We enrolled BC patients and healthy controls, recording their seafood dietary intake. DHA in form of algal oil was administered for 10 consecutive days (2 g/day). Blood samples were collected at baseline (T0) and after 10 days of supplementation (T1) to assess DHA, omega-3 index, as the sum of DHA + eicosapentaenoic acid (EPA), in red blood cells (RBC) membranes and plasma tumor necrosis factor-alpha and interleukin-6 levels. Pre- and post-treatment fatty acid profiles were obtained by gas-chromatography. Parametric and non-parametric tests were performed, as appropriate, and P-value < 0.05 was considered statistically significant. Results: Forty-three women were studied, divided into 4 groups: 11 patients with BRCA1/2 gene mutation (M group), 12 patients with familiar positive history for BC (F group), 10 patients with sporadic BC (S group), and 10 healthy controls (C group). DHA and omega-3 index increased from T0 to T1 in the 3 groups of BC patients and in controls (P < 0.001). No difference was found in DHA incorporation between each group of BC patients and between patients and controls, except for M group, which incorporated higher DHA levels with respect to controls (β = 0.42; P = 0.03). No association was documented between cytokines levels and DHA and omega-3 index at baseline and after DHA supplementation. Independent of the presence of BC, women considered as “good seafood consumers” showed at baseline DHA and omega-3 index higher with respect to “low seafood consumers” (P = 0.04; P = 0.007, respectively). After supplementation, the increase in DHA levels was greater in “low seafood consumers” with respect to “good seafood consumers” (P < 0.0001). Conclusion: DHA supplementation was associated with increased DHA levels and omega-3 index in RBC membranes of BC cancer patients, independent of the type of BC presentation, and in controls. BRCA1/2 mutation, as well as low seafood consuming habits in both BC patients and healthy controls, seem to be associated with greater ability of DHA incorporation. Larger samples of BC patients are necessary to confirm our observation.